2016
DOI: 10.1136/bmj.i673
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation groups in general practice: what are they for, where are they going?

Abstract: Millions of pounds have been spent on patient participation groups in the past five years, but is anyone listening? Stephen Gillam and Jennifer Newbould look at the evidence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…In England, patients and carers can leave feedback about their experience of a consultation with a general practitioner (GP) using a multitude of methods [1]. These include in-house surveys, the National General Practice Patient Survey, suggestion boxes, surveys for revalidation, the Friends and Family Test, Care Quality Commission ratings, and the NHS Choices and other feedback websites.…”
Section: Introductionmentioning
confidence: 99%
“…In England, patients and carers can leave feedback about their experience of a consultation with a general practitioner (GP) using a multitude of methods [1]. These include in-house surveys, the National General Practice Patient Survey, suggestion boxes, surveys for revalidation, the Friends and Family Test, Care Quality Commission ratings, and the NHS Choices and other feedback websites.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggested that the groups would benefit from clearer goals, resources, train ing and support. 12 These experiences are particularly relevant given that patient and family advisory committees are the most common way that organizations engage patients in Canada currently.…”
Section: Box 1: Considerations When Engaging Patients: Care2mentioning
confidence: 99%
“…in Building Better Participation. 8 Gillam and Newbould, in a recent article , 9 criticised the amount of money spent on PPGs. During the enhanced service period, 2011-2013, practices were paid £1.10 per patient to establish and support PPGs, but with no requirement that PPGs would actually be funded.…”
Section: Practices Need To Resource Ppgs Appropriatelymentioning
confidence: 99%